Pengelolaan Desa Wisata Pandanrejo Menuju Desapreneur - Lien Maulina; Dede Kuswandi; Siti Yulia Irani Nugraha; Hanna Daniati; Eka Rosiana (Media Wisata, 2022)
Management of Pandanrejo Tourism Village towards Desapreneur. Pandanrejo Tourism Village develops desapreneurs through village entrepreneur groups and membership, product/service capacity and quality, financial and administrative management, village development and assistance, marketing and promotion benchmarking, breadth of impact and sustainability. This study aimed to determine the management of the Pandanrejo Tourism Village and the potential and development of the Pandanrejo Tourism Village as a Desapreneur. This research was conducted using qualitative research methods, with data collection using structured interviews with tourism village managers, UMKM managers, UMKM actors, and village governments. The results showed that the management of the Pandanrejo Tourism Village has economically, socially, culturally, educationally, and environmentally, the highest benefit is provided by the social sector. Meanwhile, the economic benefits have not been felt optimally. Efforts to make the Pandanrejo Tourism Village a desapreneur include developing desapreneurs through the following aspects: group and membership of village entrepreneurs, product/service capacity and quality, financial and administrative management, village development and assistance, marketing and promotion benchmarking, breadth of impact and sustainability.